Encyclopedia of the world's endangered languages - Moseley, Christopher (Routledge, 2007)
The concern for the fast-disappearing language stocks of the world has arisen as a result of the impact of globalization. This book attempts to catalogue and describe those languages, making up the vast majority of the world's six thousand or more distinct tongues, which are in danger of disappearing.